The genus Cletocamptus (Harpacticoida, Canthocamptidae): a reappraisal, with proposal of a new subfamily, a new genus, and a new species. - Gómez, S. & B. Yáñez-Rivera (ZooKeys, 2022)
A new species of Cletocamptus closely related to C. helobius was found in sediment samples taken from a polluted estuarine system in north-western Mexico. The genus Cletocamptus was relegated to species incertae sedis in 1986, and this finding prompted us to evaluate the current taxonomic position of the genus within the Canthocamptidae. The latter has been subdivided in several, seemingly unnatural subfamilies in the past to better understand the relationships between its constituent taxa. In this study we propose a new subfamily, the Cletocamptinae subfam. nov. for Amphibiperita, Cletocamptus, and Cletocamptoides gen. nov., defined by the synapomorphic subdistal ventral spinules on the rostrum. The genus Cletocamptoides gen. nov. is proposed for C. helobius, C. merbokensis, and C. biushelo sp. nov., and is supported by the ‘cletodid’ shape of the body and the reduced one-segmented endopod of the fourth swimming leg. Cletocamptus includes all the other species with long slender spinules on the posterior margin of prosomites and with the sexually modified inner spine on the second endopodal segment of the second swimming leg in the males. Amphibiperita retained the primitive female fifth leg with exopod and baseoendopod separated, and the primitive prehensile endopod of the first leg, but is defined by the loss of the antennary exopod. Other (syn)apomorphies are given, and the evolution of the mandibular palp is briefly discussed. Additionally, a diagnosis for the new subfamily, Cletocamptinae subfam. nov., an amended narrower diagnosis for Cletocamptus, the diagnosis for Cletocamptoides gen. nov., and a phylogenetic analysis supporting the proposal of these new taxa, are given.